The value of assessing case difficulty and its effect on endodontic iatrogenic errors: a retrospective cross-sectional study. Issue 1 (1st January 2020) - Alamoudi, Ruaa A.; Alharbi, Afrah H.; Farie, Ghada A.; Fahim, Omar
ABSTRACT: The American Association of Endodontists (AAE) released a case difﬁculty assessment form to help general dentists and students treat cases within their expertise or refer advanced cases to reduce the risk of iatrogenic errors. The purpose of this study was to determine the incidence of iatrogenic complications after the use of the case difﬁculty assessment form. Arandom sample of 1000 cases that received root canal treatment in undergraduate clinics during the academicyear (2016–2017) was selected. Case difficulty assessment was made for each case before treatment onset. Once the case was approved for treatment in the undergraduate clinics, the endodontic treatments were performed following the standard procedure the endodontic department of the Dentistry School of King Abdulaziz University mandates. Digital radiographs were obtained during routine root canal treatment and were evaluated by four observers to detect any iatrogenic errors, after which the data were analyzed statistically. Iatrogenic errors were correlated signiﬁcantly with case difﬁculty ( p = 0.003), and were detected in 22.1% of all teeth treated in the undergraduate clinics. Underfilling accounted for the highestpercent of errors detected (8.4%), followed by ledge formation (4.2%). Molar teeth had the highest frequency of errors, and mesio-buccal roots of maxillary molars showed the highest percentage of errors. The AAE developed asignificantly useful tool to determine the difficulty of each case treated in undergraduate clinics, and following their recommendations will minimize the risk of iatrogenic errors.